2017
DOI: 10.1155/2017/2831056
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-9 Promotes Pancreatic Cancer Cells Proliferation and Migration via the miR-200a/Beta-Catenin Axis

Abstract: Background. Both IL-9 and miR-200a are involved in the pathogenesis of cancers; however, the role of IL-9 in pancreatic cancer and the possible underlying mechanisms remain unknown. The aim of this study was to investigate the effect of IL-9 on pancreatic cancer cells and its interaction with miR-200a. Methods. Pancreatic cancer cells (PANC-1 and AsPC-1) were treated with IL-9 and the expression of miR-200a and β-catenin in pancreatic cancer cells was measured. β-Catenin was examined as a target gene of miR-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Therefore, miR-200a is directly related with hepatic fibrosis. This finding is consistent with domestic and foreign research results [10].…”
Section: Exploring the Relationships Among Mir-200a Expression Hepatsupporting
confidence: 93%
“…Therefore, miR-200a is directly related with hepatic fibrosis. This finding is consistent with domestic and foreign research results [10].…”
Section: Exploring the Relationships Among Mir-200a Expression Hepatsupporting
confidence: 93%
“…It has been generally suggested that IL9 may inhibit the growth of solid tumors by activating the innate or adaptive immune response [55,56], while as a lymphocyte growth factor it may promote progression of hematological malignancies [10,12]. However, since IL9 has also been reported to promote proliferation of multiple solid tumor models (like pancreatic cancer, lung cancer and colitis associated cancer) [57][58][59], its anti-cancer activity may be context and tumor type specific [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether SE regulates apoptosis by regulating the expression of lncRNAs has not been further analyzed. SE-miR-200a is a proven epithelial-specific SE-derived ncRNA 8 , and miR-200a can inhibit cell apoptosis in many tumors 91 - 93 . Therefore, we speculate that SE-miR-200a is involved in the chemoresistance mechanism whereby apoptosis is inhibited in tumor cells.…”
Section: Role Of Se-derived Ncrnas In Cancermentioning
confidence: 99%